Applications of Non-thermal Atmospheric Plasma in Restorative Dentistry: A Narrative Review - Maitham Yahya Al-Tufaili; Sara Valizadeh (Institute of Medico-legal Publications Pvt Ltd, 2021)
Plasma-related technologies are essential in modern industries. Recently, plasma has attracted increasedattention in the biomedical field. Non-thermal plasma (NTP) is widely used for various therapeuticapplications in health care. Particularly in dentistry, this paper supplies an essential knowledge of plasmaand a narrative review of plasma uses in restorative dentistry. There have been efforts to use NTP technologyin restorative dentistry involving modifications of dental surfaces, adhesion, treatment of dental caries, andtooth bleaching. Although various investigations were in the recent stages, the prospective value of NTPfor dental uses has been occured. To extende the scope of plasma approaches and put suitable research topractical use, interdisciplinary research with the participation of dental professionals is recommended.